Managerial expertise, top management support and learning capacity impact on e-commerce capability and business performance. (1st January 2012) - Jehangir, Muhammad; Dominic, P.D.D.; Langove, Naseebullah; Khan, Alamgir
E-commerce (EC) embraces opportunities for the business growth. However, it brings many challenges for the usage and implementation of this technology. These challenges have a significant impact on EC success. By analysing the drivers of business performance in EC from a firm's resource perspective, the author proposed three attributes of firm's human resources that are vital for business performance in EC-based business: managerial expertise, top management support and learning capability. Defining EC capability by firm's human resources it is expected that EC contributes significantly to the firms' business performance. This paper proposes a conceptual framework to find out the human resource attributes and its contribution in developing firm's EC capability which lead to better business performance. In effect, this research provides a checklist for managers and decision-makers of the organisations to utilise the human resources and redesign their strategies for the successful EC technology.